Sosialisasi Regulasi Kegiatan Usaha Perbankan Syariah Pada Pengurus Serikat Pekerja Seluruh Indonesia Sekabupaten Karawang - Nun Harrieti; Agus Suwandono (Institut Teknologi dan Bisnis Semarang, 2023)
The community's need for economic activities based on sharia principles has been accomodated by the implementation of a dual economic system in Indonesi. This also has an impact on the banking system which carried out with a dual banking system, namely the conventional banking system and Sharia banking, and both are run side by side. Public understanding of Sharia Banking is very important considering that the majority of the Indonesian population is Muslim who has the obligation to carry out religion orders thoroughly .(kaffah) including in the economic activities. In addition, universal Sharia economics can be carried out by anyone and everywhere, which lead to the need to understand sharia banking business activities to be important. The method used is the public education method which is carried out with interactive lectures and discussion which are carried out offline at the office of the All-Indonesian Workers Union Executive in Karawang Regency which was attended by the head of the labour association. Sharia banking business activities, both in the process of collecting and distributing funds, can support the economic activities of workers, especially in the needs of economic activities based on Sharia Principles. The subject in this socialization includes regulations related to Sharia banking in Indonesia including the products offered related to sharia banking business activities